V4: Sub-basin management and governance of rainwater and small reservoirs - Venot, Jean-Philippe; Snyder, Katherine A.; Boelee, Eline (2010)
A strong international consensus has been created regarding the need for Integrated Water Resources Management (IWRM) and what it means. The river basin is then invariably singled out as the natural unit for organizing water management. Two main reasons for these shortcomings are generally presented: a lack of political will and socio-political externalities. Calls for more reforms follow but they rarely question policy models themselves. As a consequence, they face the same shortcomings they were meant to address. This project aims at understanding the processes that govern IWRM policy-making, practices and research in the Volta Basin (Ghana and Burkina Faso).